Kecemasan dan Depresi Tinggi pada Mahasiswa Kedokteran Tahap Akademik - Luthfi Rahinajati; R. Anita Indriyanti; Sadeli Masria (Bandung Conference Series: Medical Science, 2023)
Abstract. Learning pressure and assignments can cause anxiety and depression in students, which is an internal factor that can affect the learning process.This study aims to look at the differences in the levels of anxiety and depression between students at the academic level and at the professional level at the Faculty of Medicine Unisba. The sample selection technique for this study used simple random sampling with 104 research subjects. This study used a cross-sectional method with a transversal approach—a statistical test using the Mann Whitnney test.Unisba Faculty of Medicine students at the most academic stage had a moderate anxiety level of 25.5% and a mild depression level of 17.0%. In the professional background, the most moderate anxiety level was 15.8%, and an intermediate depression level of 7.0%. The results of the analysis of differences in the ranks of anxiety and depression between students at the academic level and students at the professional level at the Faculty of Medicine, Unisba, obtained a p-value = 0.001. There are differences in the incidence of anxiety and depression between FK students at the professional and academic stages. Academic stage students experience more anxiety and depression than in the professional stage. Abstrak. Tekanan belajar dan tugas dapat menimbulkan keadaan cemas dan depresi pada mahasiswa. Penelitian ini bertujuan untuk melihat perbedaan tingkat kecemasan dan depresi antara mahasiswa tahap akademik beserta mahasiswa tahap profesi Fakultas Kedokteran Unisba. Teknik pemilihan sampel penelitian ini menggunakan simple random sampling, dengan 104 orang subjek penelitian. Penelitian ini menggunakan metode cross sectional dengan pendekatan transversal. Uji statistik menggunakan uji Mann Whitnney. Mahasiswa FK Unisba tahap akademik paling banyak memiliki tingkat kecemasan sedang 25,5% dan tingkat depresi ringan 17,0%, serta pada tahap profesi paling banyak tingkat kecemasan sedang 15,8% dan tingkat depresi sedang 7,0%. Hasil analisis perbedaan tingkat kecemasan dan depresi antara mahasiswa tahap akademik beserta mahasiswa tahap profesi Fakultas Kedokteran Unisba didapatkan nilai p= 0,001. Terdapat perbedaan yang signifikan kejadian kecemasan dan depresi di antara mahasiswa FK tahap profesi dan tahap akademik.